Changes in Body Compositions and Basal Metabolic Rates during Treatment of Graves’ Disease - Min Joo Kim; Sun Wook Cho; Sumin Choi; Dal Lae Ju; Do Joon Park; Young Joo Park (International Journal of Endocrinology)
Objectives. Because thyroid hormone is an important determinant of body weight and basal metabolic rate, we investigated the changes in the basal metabolic rate and body composition sequentially after treatment for Graves’ disease. Methods. A prospective cohort study was performed with six women newly diagnosed with Graves’ disease. During a 52-week treatment of methimazole, body composition, resting respiratory expenditure (REE), and handgrip strength were measured consecutively. Results. After methimazole treatment, body weight was initially increased (0–8 weeks), subsequently plateaued (8–24 weeks), and gradually decreased in the later period (24–52 weeks) despite the decreased food intake. The measured REE was 40% higher than the predicted REE at baseline, and it gradually decreased after treatment. REE positively correlated with thyroid hormone levels, peripheral deiodinase activity, and thyroid’s secretory capacity. Body compositional analyses showed that the fat mass increased during an earlier period (4–12 weeks), while the lean mass increased significantly during the later period (26–52 weeks). Consistent with the lean mass changes, muscle strength also significantly increased during the later period. Conclusions. Treatment of Graves’ disease increased body weight and fat mass transiently with decreased REE. However, long-term compositional changes moved in a beneficial direction increasing lean mass and reinforcing muscle strength, following decreasing fat percentages.